Trigonometry
posted by Kewal .
Prove that
sin(n+1)Asin(n+2)A + cos(n+1)Acos(n+2)A = cosA

Use the same method as my other proof, but let
(n+1)A = x and
(n+2)A = y
yx = A
sin(n+1)Asin(n+2)A+cos(n+1)Acos(n+2)A
= sinxsiny + cosxcosy
= cos(yx) = cosA
Respond to this Question
Similar Questions

tigonometry
expres the following as sums and differences of sines or cosines cos8t * sin2t sin(a+b) = sin(a)cos(b) + cos(a)sin(b) replacing by by b and using that cos(b)= cos(b) sin(b)= sin(b) gives: sin(ab) = sin(a)cos(b)  cos(a)sin(b) … 
Trigonometry
I need to prove that the following is true. Thanks. csc^2(A/2)=2secA/secA1 Right Side=(2/cosA)/(1/cosA  1) = (2/cosA)/[(1cosA)/cosA] =2/cosA x (cosA)/(1cosA) =2/(1cosA) now recall cos 2X = cos^2 X  sin^2 X and we could say cos … 
Math/Calculus
Please check my work and correct any errors/point out any errors. Thanks. Solve the initialvalue problem using the method of undetermined coefficients. y''4y=e^xcos(x), y(0)=1, y'(0)=2 r^24=0, r1=2, r2=2 yc(x)=c1*e^2x+c2*e^2x … 
Mathematics  Trigonometric Identities
Let y represent theta Prove: 1 + 1/tan^2y = 1/sin^2y My Answer: LS: = 1 + 1/tan^2y = (sin^2y + cos^2y) + 1 /(sin^2y/cos^2y) = (sin^2y + cos^2y) + 1 x (cos^2y/sin^2y) = (sin^2y + cos^2y) + (sin^2y + cos^2y) (cos^2y/sin^2y) = (sin^2y … 
TRIG!
Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6 x=1  (3/4)sin^2 2x work on one side only! Responses Trig please help!  Reiny, Monday, February 23, 2009 at 4:27pm LS looks like the sum of cubes sin^6 x + cos^6 … 
Trigonometry
Prove that sin(n+1)Asin(n1)A + cos(n+1)Acos(n1)A = cos2A 
Trigonometry
1.Solve tan^2x + tan x – 1 = 0 for the principal value(s) to two decimal places. 6.Prove that tan y cos^2 y + sin^2y/sin y = cos y + sin y 10.Prove that 1+tanθ/1tanθ = sec^2θ+2tanθ/1tan^2θ 17.Prove that … 
Trigonometry desperate help, clueless girl here
2. solve cos 2x3sin x cos 2x=0 for the principal values to two decimal places. 3. solve tan^2 + tan x1= 0 for the principal values to two decimal places. 4. Prove that tan^2(x) 1 + cos^2(x) = tan^2(x) sin^2 (x). 5.Prove that tan(x) … 
MathsSs triG
Consider sin(x360)sin(90x)tan(x)/cos(90+x) 1.A.SIMPLIFY sin(x360)sin(90x)tan(x)/cos(90+x) to a single trigonometric ratio B.hence or otherwise without using a calculator,solve for X if 0<X<360. sin(x360)sin(90x)tan(x)/cos(90+x) … 
trigonometry
x×sin^3A=y , cos^3A = sinA × cosA , x×sinA= y×cosA , then prove that x^2+ y^2= 1 I have no idea